Pulmonary physiology - Levitzky, Michael G. (New York : McGraw-Hill Education/Medical, 2013)
For more than three decades, Michael Levitzky has provided medical students and residents with a solid background in the areas of pulmonary physiology essential for a thorough understanding of clinical medicine. This 8th teaches you how and why the human respiratory system works--in a style and presentation that makes it easy to absorb and integrate with your knowledge of other body systems.
Function & structure of the respiratory system -- Mechanics of breathing -- Alveolar ventilation -- Blood flow to the lung -- Ventilation-perfusion relationships -- Diffusion of gases and interpretation of pulmonary function tests -- Transport of oxygen & carbon dioxide in the blood -- Acid-base balance -- Control of breathing -- Nonrespiratory functions of the lung -- The respiratory system under stress.
'A Lange medical book.'
Includes bibliographical references and index.
Keywords: Lungs -- Physiology; Respiration; Lung -- physiology; Lung -- physiopathology; Respiration